Holocene tectonic activity along Kachchh Mainland Fault: Impact on late mature Harappan civilization, Kachchh, western India. (25th February 2019) - Kothyari, Girish Ch; Shirvalkar, Prabodh; Kandregula, Raj Sunil; Rawat, Yadubirsingh; Dumka, Rakesh K.; Joshi, Neha
Abstract: Paleoseismic and archaeological records of the Kachchh Rift Basin (KRB) of western India indicates that the region become tectonically active during the period of Middle to Late Holocene. To understand the relationship between strain accumulation, earthquake genesis, and landform development, we analyzed uplifted Late Quaternary terraces and archaeological evidence along the Kachchh Mainland Fault (KMF) zone. Dividing the elevation of the bedrock strath at each site by their ages, yields vertical uplift rates of 0.29–1.17 mm/y for the KMF zones. Archaeological data from the excavation of the Kotada Bhadli site suggest that the site was occupied during the Late mature Harappan (2300-2500 BCE) period and abandoned around 1900 BCE. The ruins of Harappan civilization at Kotada Bhadli location are resting over the Middle Holocene fluvial sediments. The oldest fluvial sediment is dated to 4 ka, whereas the youngest sediment yielded an age of 3 ka. The chronological constraints in geomorphic and archaeological records suggest that the area was hit by an earthquake around 2200 BC (∼3.5ka). The geomorphic and chronologically constrained uplift rates reveal that the KMF zone of the intraplate region of the Kachchh is geodynamically controlled by several fault segments, which are consistent with the ambient tectonic stress field owing to the northward movement of the Indian Plate concerning the Eurasian Plate.